Performance measurements of single server fuzzy queues with unreliable server using left and right method - Mueen, Zeina; Ramli, Razamin; Zabidi, Nerda Zura (AIP Publishing LLC, 2015)
There are a number of real life systems that can be described as a queuing system, and this paper presents a queuing system model applied in a manufacturing system example.The queuing model considered is depicted in a fuzzy environment with retrial queues and unreliable server.The stability condition state of this model is investigated and the performance measurement is obtained by adopting the left and right method.The new approach adopted in this study merges the existing α-cut interval and nonlinear programming techniques and a numerical example was considered to explain the methodology of this technique.From the numerical example, the flexibility of the method was shown graphically showing the exact real mean value of customers in the system and also the expected waiting times.